2006
DOI: 10.1007/s10903-006-9014-x
|View full text |Cite
|
Sign up to set email alerts
|

The Sero-Prevalence of Antibodies to Trypanosoma cruzi in Latin American Refugees and Immigrants to Canada

Abstract: We found a low sero-prevalence of Chagas' disease in a community sample of Latin American immigrants and refugees. Physicians who treat Latin American immigrants should consider the risk profile and clinical status of the individual in their decision to screen for Chagas' disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 15 publications
3
19
1
2
Order By: Relevance
“…This figure is much higher than previously reported in Canada (1%) and Germany (2%), but lower than the very high (41%) prevalence found at a referral centre in Spain [5],[22],[23]. Our finding is mostly explained by the high proportion (48%) of Bolivian migrants in the study cohort, of whom 26.2% were diagnosed with Chagas disease.…”
Section: Discussioncontrasting
confidence: 78%
“…This figure is much higher than previously reported in Canada (1%) and Germany (2%), but lower than the very high (41%) prevalence found at a referral centre in Spain [5],[22],[23]. Our finding is mostly explained by the high proportion (48%) of Bolivian migrants in the study cohort, of whom 26.2% were diagnosed with Chagas disease.…”
Section: Discussioncontrasting
confidence: 78%
“…Three out of 4 of these studies were based on samples of blood donors (Custer et al, 2012; El Ghouzzi et al, 2010; O’Brien et al, 2013) and one was a sample of pregnant women from Latin America (Edwards et al, 2013). One other study in Canada (Steele et al, 2007) used a sample of community clinics and had a prevalence similar to the PAHO based estimate. One study in France (Lescure et al, 2008) based on study volunteers from South American communities was above PAHO estimates.…”
Section: Resultsmentioning
confidence: 99%
“…Among 205 Central American immigrants living in Washington DC, 4.5% had positive T. cruzi serology (12). A study of Latin American refugees and immigrants to Canada found that 1% of 102 participants had antibodies to T. cruzi (13).…”
Section: Recommendations Of the Working Groupmentioning
confidence: 99%